Energy dependence of forward-rapidity J/[psi] and [psi](2S) production in pp collisions at the LHC - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Ohlson, Alice; et al. (The European physical journal. C, Particles and fields, 2017)
We present results on transverse momentum (pTpTp_{\mathrm {\textsc {t}}}) and rapidity (yyy) differential production cross sections, mean transverse momentum and mean transverse momentum square of inclusive J/ψJ/ψ\mathrm {J}/\psi and ψ(2S)ψ(2S)\psi \mathrm {(2S)} at forward rapidity (2.5<y<42.5<y<42.5<y<4) as well as ψ(2S)ψ(2S)\psi \mathrm {(2S)}-to-J/ψJ/ψ\mathrm {J}/\psi cross section ratios. These quantities are measured in pp collisions at center of mass energies s√=5.02s=5.02\sqrt{s}\,=5.02 and 13 TeV with the ALICE detector. Both charmonium states are reconstructed in the dimuon decay channel, using the muon spectrometer. A comprehensive comparison to inclusive charmonium cross sections measured at s√=2.76s=2.76\sqrt{s}\,=2.76, 7 and 8 TeV is performed. A comparison to non-relativistic quantum chromodynamics and fixed-order next-to-leading logarithm calculations, which describe prompt and non-prompt charmonium production respectively, is also presented. A good description of the data is obtained over the full pTpTp_{\mathrm {\textsc {t}}} range, provided that both contributions are summed. In particular, it is found that for pT>15pT>15p_{\mathrm {\textsc {t}}}>15 GeV/c the non-prompt contribution reaches up to 50% of the total charmonium yield.